FAILURE ANALYSIS OF BOILER SUPERHEATER PIPE BY MECHANICAL PROPERTIES TESTING AND CORROSION RATE TESTING - Cholis, Nur; Yunus Nasution, Ahmad; Ariani, Farida; Pakpahan, Dion (DINAMIS, 2023)
Superheater is a subcritical boiler component that functions to reheat saturated steam at constant working pressure so that it becomes saturated steam. This study aims to (1) analyze failures in superheaters, (2) test mechanical properties of superheater pipe materials, (3) calculate corrosion rates in superheater pipes with weight loss methods, (4) provide preventive maintenance solutions to minimize superheater pipe damage. The method used in this study is a qualitative approach with the type of experimental study. The method of failure analysis in this superheater pipe is by testing mechanical properties, calculating the corrosion rate of the superheater pipe and providing maintenance solutions. The results of this study are (1) the failure that occurs in this superheater pipe is the occurrence of corrosion and leakage, (2) after heat treatment with a temperature of 8500C on the superheater pipe material, the hardness value increases to 148 BHN, the impact value also increases to 43.26 joules and the phase that occurs in this material is ferrite and pearlite which shows the specimen is increasingly tenacious, (3) the corrosion rate that occurs in the superheater pipe is 0.0489 mmpy, (4) the workable maintenance solution is hardening to increase the durability and service life of the superheater pipe. Keywords: Superheater, Noise, Mechanical Properties, Heat treatment.